2012
DOI: 10.1038/ncomms2090
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA-212/132 family regulates both cardiac hypertrophy and cardiomyocyte autophagy

Abstract: Pathological growth of cardiomyocytes (hypertrophy) is a major determinant for the development of heart failure, one of the leading medical causes of mortality worldwide. Here we show that the microRNA (miRNA)-212/132 family regulates cardiac hypertrophy and autophagy in cardiomyocytes. Hypertrophic stimuli upregulate cardiomyocyte expression of miR-212 and miR-132, which are both necessary and sufficient to drive the hypertrophic growth of cardiomyocytes. MiR-212/132 null mice are protected from pressure-over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
429
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 550 publications
(450 citation statements)
references
References 45 publications
10
429
0
5
Order By: Relevance
“…MiRNAs are essential to the regulation of cardiac remodeling; [3][4][5][6][7][8] however, many of them have not been well characterized. We previously demonstrated that miR-221 induces cardiomyocyte hypertrophy in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are essential to the regulation of cardiac remodeling; [3][4][5][6][7][8] however, many of them have not been well characterized. We previously demonstrated that miR-221 induces cardiomyocyte hypertrophy in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…2 A large body of evidence indicates that miRNA-mediated gene regulation has important roles in the control of cardiac homeostasis and pathological remodeling. [3][4][5][6][7][8] We previously found that miR-221 is significantly upregulated in patients with hypertrophic cardiomyopathy (HCM) and in a mouse model of cardiac hypertrophy and heart failure induced by pressure overload. The in vitro overexpression of miR-221 alone is sufficient to increase the size of cardiomyocytes, accompanied by enhanced expression levels of atrial natriuretic polypeptide (ANP) and brain natriuretic peptide (BNP).…”
mentioning
confidence: 99%
“…Thum's group elegantly showed that miRNA-212/132 inhibits autophagy in cardiomyocytes by targeting FoxO3a. Pharmacological inhibition of miR-132 reduced cardiac hypertrophy and heart failure induced by pressure overload (14). In addition, exosome-mediated miR-145 administration was found to reduce ischemic injury by activating autophagy (15).…”
mentioning
confidence: 97%
“…Gupta et al employed an aged mice model to study the effect of anti-miR22 therapy following AMI and, compared to younger mice, old mice were shown to have higher expression levels of miR-22, a key regulator for cardiac autophagy [65]. for the cardiac hypertrophy in HF murine models [69]. Intriguingly, this study showed that, by inhibiting miR-132, the heart showed decreased cardiac fibrosis and preserved cardiac function and dilatation, eventually preventing the development of pressure overload-induced HF.…”
Section: Mir-based Therapy For Cardiovascular Diseasesmentioning
confidence: 99%